DIAGNOSTIC SIGNIFICANCE OF ST-SEGMENT DEPRESSION IN LEAD A VR FOR IDENTIFYING CULPRIT ARTERIES IN INFERIOR WALL ST-ELEVATION MYOCARDIAL INFARCTION - Dr. Mohsin Iqbal; Dr. Farhat Ullah Khan; Dr. Ayesha Bibi; Dr. Naeem Khan; Dr. Muhammad Idrees Khan; Dr. Rahim Dil Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: A blockage in either the right coronary artery (RCA) or left circumflex artery (LCx) creates the most frequent cause of inferior wall ST-elevation myocardial infarction (IW-STEMI). The necessity to recognize the affected artery rapidly permits immediate treatment. The measurement of ST segment depression in the lead aVR proves valuable as an indicator during these circumstances.Objective: The study evaluates whether ST-segment depression in lead aVR helps diagnose the blockage artery for IW-STEMI patients.Material and Methods: Descriptive cross-sectional research occurred at multi centers including Department of Cardiology, Ayub Teaching Hospital, Abbottabad and Hayatabad Medical Complex, Peshawar in the duration from January, 2023 to December, 2023. The research analysis included 150 IW-STEMI patient participants. Experts examined the ST depression in lead aVR through ECGs to find correlations with angiographic results.Result: The diagnosis of Left Coronary Artery blockage with ST depression in lead aVR showed 88.6% sensitivity while offering 55.0% specificity. The evidence shows that when lead aVR displays depressed waves, it suggests that the LCx artery is blocked (p